Molecular Characterization of an NADPH-Dependent Acetoin Reductase/2,3-Butanediol Dehydrogenase from Clostridium beijerinckii NCIMB 8052 - Raedts, John (American Society for Microbiology, 2014)
Acetoin reductase is an important enzyme for the fermentative production of 2,3-butanediol, a chemical compound with a very broad industrial use. Here, we report on the discovery and characterization of an acetoin reductase from Clostridium beijerinckii NCIMB 8052. An in silico screen of the C. beijerinckii genome revealed eight potential acetoin reductases. One of them (CBEI_1464) showed substantial acetoin reductase activity after expression in Escherichia coli. The purified enzyme (C. beijerinckii acetoin reductase [Cb-ACR]) was found to exist predominantly as a homodimer. In addition to acetoin (or 2,3-butanediol), other secondary alcohols and corresponding ketones were converted as well, provided that another electronegative group was attached to the adjacent C-3 carbon. Optimal activity was at pH 6.5 (reduction) and 9.5 (oxidation) and around 68°C. Cb-ACR accepts both NADH and NADPH as electron donors; however, unlike closely related enzymes, NADPH is preferred (K(m), 32 μM). Cb-ACR was compared to characterized close homologs, all belonging to the “threonine dehydrogenase and related Zn-dependent dehydrogenases” (COG1063). Metal analysis confirmed the presence of 2 Zn(2+) atoms. To gain insight into the substrate and cofactor specificity, a structural model was constructed. The catalytic zinc atom is likely coordinated by Cys(37), His(70), and Glu(71), while the structural zinc site is probably composed of Cys(100), Cys(103), Cys(106), and Cys(114). Residues determining NADP specificity were predicted as well. The physiological role of Cb-ACR in C. beijerinckii is discussed.